2015
DOI: 10.1146/annurev-cellbio-100913-013409
|View full text |Cite
|
Sign up to set email alerts
|

Prions: What Are They Good For?

Abstract: Prions, a self-templating amyloidogenic state of normal cellular proteins such as PrP, have been identified as the basis of a number of disease states, particularly diseases of the nervous system. This finding has led to the notion that protein aggregation, namely prionogenic aggregates and amyloids, is primarily harmful for the organism. However, identification of proteins in a prion-like state that are not harmful and may even be beneficial has begun to change this perception. This review discusses when and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 112 publications
(131 reference statements)
2
42
0
Order By: Relevance
“…That being stated, it is useful to outline key requirements for establishing a model, in order to have an objective yardstick for assessing the conclusiveness of current data, which have been discussed and/ or reviewed in recent articles. 9,10 (a) Synaptic activity that triggers long-term memory should be demonstrated to result in conformational switch of CPEB from a monomeric to oligomeric prion-like form at active but not at inactive synapses. (b) At the activated synapse, the new oligomeric CPEB should be capable of self-renewal, recruiting monomeric CPEB into oligomers over the extended period for which memory is retained.…”
Section: Characterization Of Prions and Prion Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…That being stated, it is useful to outline key requirements for establishing a model, in order to have an objective yardstick for assessing the conclusiveness of current data, which have been discussed and/ or reviewed in recent articles. 9,10 (a) Synaptic activity that triggers long-term memory should be demonstrated to result in conformational switch of CPEB from a monomeric to oligomeric prion-like form at active but not at inactive synapses. (b) At the activated synapse, the new oligomeric CPEB should be capable of self-renewal, recruiting monomeric CPEB into oligomers over the extended period for which memory is retained.…”
Section: Characterization Of Prions and Prion Domainsmentioning
confidence: 99%
“…Such a model has been proposed and is supported by several observations of the prion-domain containing RNA regulatory protein CPEB. 9,10 This review will introduce diverse aspects of molecular biology of long-term memory, discuss the role of translational control mechanisms in long-term synaptic plasticity with a particular focus on the role and potential mechanisms by which prion-domain containing RNA-binding proteins enable longterm memory formation and retention.…”
Section: Introductionmentioning
confidence: 99%
“…The type of protein involved in this benign aggregation is known as a functional amyloid, or prion. Although it undergoes conformational changes and organized polymerization, it is an important player in many processes, such as memory consolidation (CPEB, CPEB3, and Orb2), the immune response to viral infection (mitochondrial antiviral signaling protein (MAVS)), and hormone transport (Pmel17) (7)(8)(9)(10). Yeast prions have such characteristics, and there are several important reviews on this subject (11,12).…”
mentioning
confidence: 99%
“…Several recent studies have expanded the prion-like amyloid aggregation research to cancer because of the aggregation of p53 and other tumor suppressors (6,(22)(23)(24). This correlation between misfolding/aggregation and nucleic acid binding is not restricted to pathological events and serves some routine functions, including the persistence of long-term memory, as in the case of CPEB in Aplysia and CPEB3 in mammals (10), as well as the amyloid-like aggregation of the RNA-binding protein Rim4, involved in gametogenesis (25). Recently, it was shown that several different amyloid fibrils induce the release of extracellular traps of chromatin from neutrophils (26).…”
mentioning
confidence: 99%
“…Nucleic acid reactivity clearly depends on the protein assembly state and to some extent on the protein sequence. Based on the idea that the amyloid fold is ancient and may have co-evolved with RNAs [110,111], it is plausible to propose that such proteins present a general nucleic acid binding property resulting from this evolution process. NA-binding can thus result in ribonucleoprotein complexes that possess important cellular functions, for instance, being related to functional amyloids [112] or to amyloidogenic diseases [99].…”
Section: Discussionmentioning
confidence: 99%